Pemetaan dan strategi kebijakan: dampak kerusakan tanah untuk produksi biomasa di Kota Depok - Tatan Sukwika; Irman Firmansyah (Universitas Negeri Malang, 2020)
Depok area was planned to had a harmonious use of space between settlements, socio-economic activities and conservation efforts. The rapid growth of the region had implications for land needs, including conversion of agricultural land. The area indicated with high potential for soil damage for biomass production was the Sawangan district. The purpose of study was the mapping of policy strategies for preventing soil damage for biomass production. The method used was survey mapping and descriptive analysis. The result shows that status of land damage for biomass production was categorized as moderate and high category. The priority policy was to reduce the use of chemical fertilizers and the application of liming before planting. The recommendation was that the